"Courage in ignorance": Mothers' retrospective accounts of early childbearing in Turkey - Serap Kavas (Comparative Population Studies (CPoS), 2022)
Although extensive research investigates the consequences of teenage motherhood, there is still very limited research exploring young mothers' experiences in their own voices. This gap is particularly evident for those non-Western developing countries in which women's voices are largely muted. This paper explores women's perceptions and evaluations of their early motherhood, drawing on their lived experiences and retrospective accounts. This study also investigates how early first birth influences these mother's subsequent fertility. The study adopts a qualitative method based on interviews with a total of 17 women in several cities in Turkey who had their first birth at a young age (ages 17-22). A qualitative approach is most suitable for this research area, which aims to explore young mothers' interpretations of their fertility timing and the consequences of this event for their lives in general, including subjective evaluations and subtle meanings. A key finding of this study is that the interviewees describe early childbearing as a negative event in their life course, convey regret for having had an early first birth, and report a feeling of dissatisfaction with being a young mother. A second finding concerns the influence of early first birth on subsequent childbearing. The women's accounts indicate that subsequent fertility operated as a compensation for the missed feelings of motherhood and served as an opportunity to heal from hurtful experiences. This study points to the importance of social context in determining the consequences of early fertility.
urn:nbn:de:bib-cpos-2022-02en8
Keywords: 300; Qualitative interviews; Retrospective accounts; Turkey; Young motherhood